„Die Prüfungen werden mich sicherlich nicht zu einer besseren Lehrkraft machen.“ Wie beurteilen Studierende Prüfungen und Feedback im Lehramtsstudium? - Vogelsang, Christoph; Janzen, Thomas; Meier, Jana; Wotschel, Philipp (Sektionstagung empirische Bildungsforschung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF) sowie der Kommission für Bildungsplanung, Bildungsorganisation und Bildungsrecht (KBBB))

Der Zyklus von Planung und Reflexion. Zusammenhänge zwischen der generischen Unterrichtsplanungsfähigkeit und der Reflexionskompetenz angehender Lehrkräfte.

Show, don't tell - Rollenspielbasierte Simulationsprüfungen für zukünftige Englischlehrkräfte (Poster) - Janzen, Thomas; Meier, Jana; Rumlich, Dominik; Vogelsang, Christoph; Wotschel, Philipp (30. DGFF Kongress 2023)

Welche Rolle spielt eine reflexive Haltung für eine qualitätsvolle Unterrichtsreflexion? – Zusammenhänge zwischen einer quasi-experimentellen Einstellung und der Reflexionsperformanz von Lehramtsstudierenden [Einzelbeitrag]. - Meier, Jana; Vogelsang, Christoph; Küth, Simon; Scholl , Daniel; Watson, Christina; Seifert, Andreas

Rollenspielbasierte Simulationen als Übungs- und Prüfungsformate im Lehramtsstudium. Eine explorative Studie zu Erfahrungen und Einschätzungen aus Studierendensicht. - Meier, Jana; Janzen, Thomas; Wotschel, Philipp; Vogelsang, Christoph (die hochschullehre)

"Intersectionality and Fourth-Wave Feminism in Bernardine Evaristo's Girl, Woman, Other" - Strauß, Sara (Women: A Cultural Review)

Tailoring Pore Size and Catalytic Activity in Cobalt Iron Layered Double Hydroxides and Spinels by Microemulsion‐Assisted pH‐Controlled Co‐Precipitation - Rabe, Anna; Jaugstetter, Maximilian; Hiege, Felix; Cosanne, Nicolas; Ortega, Klaus Friedel; Linnemann, Julia; Tschulik, Kristina; Behrens, Malte (ChemSusChem)
Cobalt iron containing layered double hydroxides (LDHs) and spinels are promising catalysts for the electrochemical oxygen evolution reaction (OER). Towards development of better performing catalysts, the precise tuning of mesostructural features such as pore size is desirable, but often hard to achieve. Herein, a computer‐controlled microemulsion‐assisted co‐precipitation (MACP) method at constant pH is established and compared to conventional co‐precipitation. With MACP, the particle growth is limited and through variation of the constant pH during synthesis the pore size of the as‐prepared catalysts is controlled, generating materials for the systematic investigation of confinement effects during OER. At a threshold pore size, overpotential increased significantly. Electrochemical impedance spectroscopy (EIS) indicated a change in OER mechanism, involving the oxygen release step. It is assumed that in smaller pores the critical radius for gas bubble formation is not met and therefore a smaller charge‐transfer resistance is observed for medium frequencies.
Keywords: electrocatalysis; oxygen evolution reaction; cobalt spinel; cobalt hydroxide; LDH

Open time studies of cold curing polyurethane adhesives using a standardized spatula test setup suitable for near-production conditions - Mahnel, Sabrina; Bannert, Franz; Zimmermann, Johannes; Grunder, Sergio; Demmig, Martin; Lomolino, Silvia; Grundmeier, Guido (International Journal of Adhesion and Adhesives)

Umgang mit Evidenzen angehender Lehrkräfte in den Naturwissenschaften: Epistemologie in der Lehrkräfteausbildung - Pollmeier, Pascal

Exploring Platform Types and Related Concepts in Service Research – A Systematic Scoping Literature Review - Hansmeier, Philipp (Proceedings of the 18th International Conference on Wirtschaftsinformatik (WI23))

Highly Tunable 4-Phosphoryl Pyrazolone Receptors for Selective Rare-Earth Separation - Zhang, Jianfeng; Wenzel, Marco; Schnaars, Kathleen; Hennersdorf, Felix; Lindoy, Leonard F.; Weigand, Jan J. (Inorganic Chemistry)
Highly selective rare-earth separation has become increasingly important due to the indispensable role of these elements in various cutting-edge technologies including clean energy. However, the similar physicochemical properties of rare-earth elements (REEs) render their separation very challenging, and the development of new selective receptors for these elements is potentially of very considerable economic and environmental importance. Herein, we report the development of a series of 4-phosphoryl pyrazolone receptors for the selective separation of trivalent lanthanum, europium, and ytterbium as the representatives of light, middle, and heavy REEs, respectively. X-ray crystallography studies were employed to obtain solid-state structures across 11 of the resulting complexes, allowing comparative structure–function relationships to be probed, including the effect of lanthanide contraction that occurs along the series from lanthanum to europium to ytterbium and which potentially provides a basis for REE ion separation. In addition, the influence of ligand structure and lipophilicity on lanthanide binding and selectivity was systematically investigated via n-octanol/water distribution and liquid–liquid extraction (LLE) studies. Corresponding stoichiometry relationships between solid and solution states were well established using slope analyses. The results provide new insights into some fundamental lanthanide coordination chemistry from a separation perspective and establish 4-phosphoryl pyrazolone derivatives as potential practical extraction reagents for the selective separation of REEs in the future.

TPACK, DPACK, XY-PACK? Eine kritische Auseinandersetzung mit der Modellierung digitaler Inhaltskompetenzen für die berufliche Bildung - Sänger, Niklas

Verschränkung wie am Fließband - Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physik in unserer Zeit)

How organisations regulate Muslim body practices: a comparison of schools, hospitals, and swimming pools - Apelt, Maja; Koch, Annika; Michalowski, Ines; Molzberger, Kaspar; Schenk, Liane; Schmidt, Max Oliver (Comparative Migration Studies)
Abstract In a comparison of three human service organisations in which the human body plays a key role, we examine how organisations regulate religious body practices. We concentrate on Muslim norms of dressing and undressing as a potential focal point of cultural and religious diversity. Inspired by Ray’s (2019) idea of racialized organizations, we assume that state-run organizations in Germany are characterized by a strong commitment to religious tolerance and non-discrimination but also marked by anti-Muslim sentiment prevalent among the German population. Our study looks for mechanism that explain how Human Service Organizations accommodate Muslim body practices. It draws on qualitative empirical data collected in state-run hospitals, schools and swimming pools in Germany. Our analyses show that the organizations draw on formal and informal rules at the organizational level to accommodate Islam. We identify five general organizational mechanisms that may hinder Muslim accommodation in human service organizations. In particular, we see a risk of decoupling between the expectation of religious tolerance and processes that lead to informal discrimination, driven mainly by the difficulty of controlling group dynamics among users.

Ramadan in der Schule – Widersprüchliche Anforderungen und schulische Reaktionen - Apelt, Maja; Koch, Annika (Organisation zwischen Theorie und Praxis)

Effect of a controlled lifestyle intervention on medication use and costs: The Healthy Lifestyle Community Program (cohort 2) - Kranz, Ragna-Marie; Kettler, Carmen; Anand, Corinna; Koeder, Christian; Husain, Sarah; Schoch, Nora; Buyken, Anette; Englert, Heike (Nutrition and Health)
Background: Establishing a healthy lifestyle has a great potential to reduce the prevalence of non-communicable diseases (NCDs) and their risk factors. NCDs contribute immensely to the economic costs of the health care system arising from therapy, medication use, and productivity loss. Aim: The aim of this study was to evaluate the effect of the Healthy Lifestyle Community Program (cohort 2; HLCP-2) on medication use and consequently on medication costs for selected NCDs (diabetes, hypertension, and dyslipidemia). Methods: Data stem from a 24-month non-randomised, controlled intervention trial aiming to improve risk factors for NCDs. Participants completed questionnaires at six measurement time points assessing medication use, from which costs were calculated. The following medication groups were included in the analysis as NCD medication: glucose-lowering medications (GLM), antihypertensive drugs (AHD) and lipid-lowering drugs (LLD). Statistical tests for inter- and intra-group comparison and multiple regression analysis were performed. Results: In total, 118 participants (intervention group [IG]: n = 79; control group [CG]: n = 39) were considered. Compared to baseline medication use decreased slightly in the IG and increased in the CG. Costs for NCD medication were significantly lower in the IG than in the CG after 6 ( p = 0.004), 12 ( p = 0.040), 18 ( p = 0.003) and 24 months ( p = 0.008). After multiple regression analysis and adjusting for confounders, change of costs differed significantly between the groups in all final models. Conclusion: The HLCP-2 was able to moderately prevent an increase of medication use and thus reduce costs for medication to treat NCDs with the greatest impact on AHD. Trial registration German Clinical Trials Register DRKS ( www.drks.de ; reference: DRKS00018775).

Electrically controlling vortices in a neutral exciton polariton condensate at room temperature - Zhai, Xiaokun; Ma, Xuekai; Gao, Ying; Xing, Chunzi; Gao, Meini; Dai, Haitao; Wang, Xiao; Pan, Anlian; Schumacher, Stefan; Gao, Tingge (Physical Review Letters)

Room-Temperature Electrical Field-Enhanced Ultrafast Switch in Organic Microcavity Polariton Condensates - De, Jianbo; Ma, Xuekai; Yin, Fan; Ren, Jiahuan; Yao, Jiannian; Schumacher, Stefan; Liao, Qing; Fu, Hongbing; Malpuech, Guillaume; Solnyshkov, Dmitry (Journal of the American Chemical Society (JACS))
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Circularly Polarized Lasing from a Microcavity Filled with Achiral Single‐Crystalline Microribbons - Liang, Qian; Ma, Xuekai; Long, Teng; Yao, Jiannian; Liao, Qing; Fu, Hongbing (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

(Re-)inventing Biblical Traditions: The Representation of Pontius Pilate in Contemporary Historical Fiction. - Behler, Felix (Narrative Ethics and Character in the Representation of the Past in Contemporary Fiction. Organisation: Dr. Christine Berberich (University of Portsmouth), Dr. Armelle Parey (Universite de Caen Normandie).)